RESEARCH ON DAMAGE DEGREE ASSESSMENT METHOD OF ROLLING BEARING INNER RING BASED ON DIAGONAL SLICE SPECTRUM AND GREY RELATIONAL GRADE - JIANG ZhangLei; WU YaPeng; WANG JiFang; XU XiaoLi (Jixie qiangdu)
Aiming at the problem that the fault information of rolling bearing was weak and susceptible to noise, which was difficult to judge the damage degree of bearing failure, a new method was proposed. Bearing fault location and damage diameter size could be obtained using the method based on third-order cumulant diagonal slice spectrum and gray correlation theory. Bearing fault location information could be determined using the characteristics of third-order cumulant diagonal slice spectrum to suppress the Gaussian noise and to identify the secondary phase coupling signal. And gray relational theory was used to analyze the kurtosis index, the pulse index and the margin index of the third-order cumulant diagonal section data to obtain the curve of the damage degree. Finally, actual signal is analyzed to obtain the bearing fault location and the damage diameter, which indicates the feasibility and practicability of the method.